Use of GDOES method for evaluation of the quality and thickness of hot dip galvanised coating. (2nd November 2018) - Vontorová, J.; Mohyla, P.
ABSTRACT: The paper describes an assessment of thickness and quality of hot-dip galvanised coating by means of the glow discharge optical emission spectrometry method (GDOES). For comparison, a metallographic analysis was made using an optical microscope. An important factor influencing thickness and quality of the hot-dip galvanised coating is chemical composition of steel, particularly the amounts of silicon. Structural steels with a low amount of silicon S235JR and S355J2 were chosen for the experiment and high-strength steel S690QL with a high amount of silicon was chosen for comparative purposes. The results of the coating thickness measurement by means of GDOES and optical microscopy show only minimal differences. Steel S690QL shows a thick and uneven zinc coating. In the case of steels S235JR and S355J2 an optimal hot-dip galvanised coating was observed.